Strategi Keberlanjutan Obyek Wisata Melalui Tata Lansekap Studi Kasus Desa Karangmalang Sragen - Aminaturosyida Rahma Wardhani; Musyawaroh Musyawaroh; Tri Joko Daryanto; Sumaryoto Sumaryoto; Ummul Mustaqimah; Made Suastika (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
This research focused on landscape design plan  to improve the sustainability of a tourist object. The method used is a programmed design which includes determining the problem, collecting relevant data and information, analyzing design decisions and ending with the determination of a landscape design plan. The data and information obtained consist of factual data, namely tourism activity programs, village tourism potential, landscape constraints for tourism sustainability, as well as normative data, namely spatial planning of tourist objects, sustainability principles, and landscape governance principles. The results of the analysis consist of determining the landscape theme, determining the type of vegetation design, and determining the variation of plant placement by criteria of tourism attributes and sustainability aspects.